Does the Weighted Rope Jump Training Affect the Motor Skills in Adolescent Female Volleyball Players? - Filiz Fatma Colakoglu; Selma Karacan; Nevin Atalay Guzel; Gul Baltaci (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2017)
The aim of this study was to investigate the effect of a 12-week rope jumping and weighted rope jumping  exercise programme on body composition and strength performance in 25 female adolescent volleyball players. Group 1 was trained on the weighted rope jumping (WRJ;(n=8)) diet as well as volleyball training, Group 2 on rope jumping (RJ;(n=9)) diet as well as volleyball training and Group 3, the control (C;(n=8)), participated only volleyball training. Percentage body fat and subsequent fat free mass by Sloan and Weir's equation,the hand grip strength by Takei Grip -D trade mark hand dynamometer, sit-ups and push-ups for endurance and standing long jump, Sergeant Jump, and medicine ball javelin tests for lower and upper extremity muscular strength were applied before and after training. There was no difference in the body weight of the three groups although there was a considerable decrease of the body fat of WRJ and RJ groups (p<0,01).WRJ group was highly increased for the mean of sit-ups,standing long jump and the values of throwing the ball to the front part with two hands (p<0,01). There were significant differences in the values of push-up, right hand grip strength and the values of left hand grip strength in WRJ and C groups (p<0,01).In  this  study  we  showed  that  the  muscles  in  upper  extremity,  lower  extremity  and  abdominal  region of a group doing exercises for 12-week programme with weighted rope would be gained a considerable power.